The causal relationship between gut microbiota and bone mineral density: a Mendelian randomization study - Wang, Ying; Zhang, Xuejian; Tang, Guangjun; Deng, Pin; Qin, Yuyan; Han, Jinglu; Wang, Shulong; Sun, Xiaojie; Li, Dongxiao; Chen, Zhaojun (Frontiers in Microbiology, 2023)
The gut microbiota has emerged as an intriguing and potentially influential factor in regulating bone health. However, the causal effect of the gut microbiota on bone mineral density (BMD) appears to differ throughout various life stages.Methods: We conducted a Mendelian randomization (MR) analysis to investigate the potential causal relationship between gut microbiota and BMD in five distinct age groups: 0-15 years, 15-30 years, 30-45 years, 45-60 years, and 60 years and older. The analysis employed three different methods, namely MR-Egger, Weighted median, and Inverse-variance weighting, to ensure the robustness of our findings, a series of sensitivity analyses were also conducted, such as horizontal pleiotropy tests, heterogeneity tests, and leave-one-out sensitivity tests.Results: In the age group of 0-15 years, Eubacterium_fissicatena_group and Eubacterium_hallii_group were identified as risk factors for BMD. During the 15-30 age group, Phascolarctobacterium, Roseburia, and Ruminococcaceae_UCG_003 were found to be protective factors for BMD. In the 30-45 age group, Lachnospira genus demonstrated a protective effect on BMD, while Barnesiella and Lactococcus were identified as risk factors for BMD. Moving on to the 45-60 age group, Eubacterium_ventriosum_group, Lachnospiraceae_UCG_004, and Subdoligranulum were observed to be protective factors for BMD, while Eubacterium_coprostanoligenes_group, Fusicatenibacter, and Lactococcus were associated with an increased risk of BMD. In individuals aged 60 years and older, Fusicatenibacter and Ruminococcaceae_UCG_002 were also noted as risk factors for BMD. Conversely, Eubacterium_ruminantium_group, Ruminococcus_gauvreauii_group, Alistipes, and Coprococcus_3 were found to be protective factors for BMD, whereas Barnesiella and Sellimonas were identified as risk factors for BMD.Conclusions: A robust causal relationship between gut microbiota and bone mineral density (BMD) exists throughout all stages of life, with Firmicutes phylum being the primary group associated with BMD across age groups. Gut microbiota linked with BMD primarily belong to the Firmicutes phylum across age groups. The diversity of gut microbiota phyla associated with BMD depicts relatively stable patterns during the ages of 0-45 years. However, for individuals aged 45 years and above, there is an observed increase in the number of gut microbiota species linked with BMD, and by the age of 60 years, a trend towards an increase in the Bacteroidetes phylum categories is proposed.